PELAKSANAAN PENSERTIPIKATAN TANAH SISTEMATIS LENGKAP DI KANTOR PERTANAHAN KABUPATEN PASAMAN BARAT - Boiziardi AS, Ronal Arifin dan (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
The role of land in national development, both as a place to live and for business activities. To carry out land registration for land owners and in order to guarantee legal certainty in the land sector and aims to find out how the systematic land registration process is complete. The method used is an empirical juridical approach. Based on the results of the research and discussion, it can be concluded as follows, the implementation of systematic and complete land certification at the Land Office of West Pasaman Regency through several stages of location determination, formation of an adjudication committee, counseling, collection of physical data and juridical data, land inspection, announcement of physical and juridical data, issuance of decisions granting land rights, bookkeeping of land rights, determination of land rights certificates and submission of land rights certificates. As well as the obstacles faced by the implementation team of the physical task force and the juridical task force as well as efforts to overcome obstacles to the complete systematic land registration process at the West Pasaman Regency Land Office.